THE GENERATIVE AI DISRUPTION: A BIBLIOMETRIC ANALYSIS of ARTIFICIAL INTELLEGENCE TRANSFORMATIVE IMPACT ON HOSPITALITY RESEARCH AND PRACTICE - Audio Valentino Himawan Marhendra (Bajang Institute, 2025)
This study provides a comprehensive bibliometric analysis of Artificial Intelligence's transformative impact on hospitality research. Utilizing 3,993 documents from the Scopus database (2011-2025), we map the field's intellectual structure and evolution. Findings reveal exponential publication growth since 2017 and a structure defined by foundational